Size spectra in tropical streams: effects of land use changes - Resende, Giovanna Collyer (2022)
Changes in land use have altered the structure and functioning of ecosystems, including trophic interactions that control the flow of matter and energy. We investigated the differences between the relationship of log10-biomass and log10-body size classes (size spectrum) of impacted and preserved streams along a land use gradient, going from almost complete coverage by native forest to complete agriculture of monocultures. The size spectrum characterizes how many organisms of each size class are maintained in the communities and is therefore a way of accessing the energy flow between trophic levels. We used data from macroinvertebrates of 30 streams, located in southeastern Brazil. We predicted that impacted streams could have more or less basal resources available (i.e. higher or lower size spectra intercept, respectively), and in both cases we expected a higher energetic cost, sustaining less biomass in large size classes (i.e. steeper size spectra slope). We also expected more deviations in the model in impacted streams (lower regression R²), due to the high energy demand and low energy efficiency transfer, causing organisms to feed outside their ideal predator–prey mass ratio. Our results demonstrated that impacted streams have fewer small organisms available at lower trophic levels (lower intercepts) than preserved streams, but with a more efficient energy transfer (shallower slopes). This may be due to few strong interaction links related to communities with less diversity and the simplification of the food web in impacted environments, which tends to decrease stability and enhance vulnerability to stochastic events. Preserved streams are more complex and have more energy pathways possible, resulting in weaker interaction strengths, which leads to a higher community stability. We also demonstrated that deviations in the model do not vary systematically across the land use gradient, as well as its structure is not defined by the land use type. Our study represents a step forward to understand how anthropogenic impacts affect trophic interactions and ecosystem functioning in tropical streams.